GDF-15: A Potential Biomarker and Therapeutic Target in Systemic Lupus Erythematosus - Xu, Wang-Dong; Huang, Qi; Yang, Chan; Li, Rong; Huang, An-Fang (Frontiers in Immunology, 2022)
Systemic lupus erythematosus (SLE) is a rheumatic disease. Growth differentiation factor 15 (GDF-15) is a member of transforming growth factor-β superfamily. To date, association of GDF-15 with SLE pathogenesis is not clarified. This study discussed GDF-15 serum levels and gene polymorphisms in SLE patients and lupus mouse model further demonstrated the role of GDF-15 in lupus development. We conducted two independent case-control studies for SLE patients. One is to evaluate serum levels of GDF-15 in 54 SLE patients and 90 healthy controls, and the other one is to analyze gene polymorphisms of GDF-15 in 289 SLE patients and 525 healthy controls. Serum levels of GDF-15 were detected by ELISA. GDF-15 gene polymorphisms (rs1055150, rs1058587, rs1059519, rs1059369, rs1227731, rs4808793, and rs16982345) were genotyped by the Kompetitive Allele-Specific PCR (KASP) method. Addition of recombinant GDF-15 into pristane-induced lupus mice evaluated histological and serological changes. Results showed that serum levels of GDF-15 were overexpressed in SLE patients and associated with disease activity. Polymorphisms rs1055150, rs1059369, rs1059519, and rs4808793 of GDF-15 gene were related to SLE risk. Lupus mice showed splenomegaly, severe histological scores, and high levels of autoantibodies [antinuclear antibodies (ANA) and total immunoglobulin G (IgG)], whereas administration of GDF-15 into lupus mice reduced the histological changes. Percentages of CD8+, CD11b+, CD19+, CD11C+ cells, TH2 cells, and pro-inflammatory cytokines (IL-1β, IL-2, IL-4, IL-21, and IL-22) were reduced after GDF-15 treatment in lupus mice. In conclusion, GDF-15 was related to lupus pathogenesis and inhibited lupus development.